2006
DOI: 10.1007/s10709-005-2611-0
|View full text |Cite
|
Sign up to set email alerts
|

Ecological–genetic feedback in DNA repair in wild barley, Hordeum spontaneum

Abstract: Regulation of genetic variation in natural populations is a problem of primary importance to evolutionary biology. In the reported study, the repair efficiency of double strand DNA breaks was compared in six wild barley accessions from Israeli natural populations of H. spontaneum: three from mesic populations (one from Maalot and two from Mount Meron, Upper Galilee) and three from xeric populations (one from Wadi Quilt in the Judean Desert and two from Sede Boqer, in the northern Negev Desert). Pulsed field ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 45 publications
(49 reference statements)
1
12
0
Order By: Relevance
“…Likewise, we found the higher mutation rates described previously (9) and here, higher gene conversion, crossing-over (32), DNA repair (33,34), genome size, retrotransposons, and up-regulation in genome-wide gene expression of yeasts under H 2 O 2 stress (35) on the more stressful AS/SFS. Clearly, more stressful environments generate higher diversities across the genome.…”
Section: Discussionsupporting
confidence: 89%
“…Likewise, we found the higher mutation rates described previously (9) and here, higher gene conversion, crossing-over (32), DNA repair (33,34), genome size, retrotransposons, and up-regulation in genome-wide gene expression of yeasts under H 2 O 2 stress (35) on the more stressful AS/SFS. Clearly, more stressful environments generate higher diversities across the genome.…”
Section: Discussionsupporting
confidence: 89%
“…46 Altogether, the results in B. simplex suggest similar interslope adaptive divergence at a microscale where ecological stress causes adaptive and speciational divergence by climatic selection.…”
Section: Drosophilamentioning
confidence: 78%
“…These patterns represent adaptive life-strategies contributing to higher fitness. 46 Incipient postzygotic isolation has been recently found in D. melanogaster at EC by Pechkovsky. 32 Interslope hybrid populations displayed lower fitness than slope-specific hybrid populations in some traits, e.g.…”
Section: Prezygotic Sexual and Reproductive Behavior Isolation And Imentioning
confidence: 96%
“…The results suggest the relationship between DNA repair efficiency and thermotolerance with thermotolerant lines tended to repair DNA more efficiently than thermosensitive lines. On a regional scale across Israel, in wild barley H. spontaneum, it was shown that climatically stress-adapted genotypes displayed DNA repair efficiency more significantly (37). Additional evidence is required in more model organisms to substantiate the link between stress tolerance and DNA repair efficiency, as indicated in these initial experiments and, most importantly, to unfold the involved mechanism of DNA repair.…”
Section: Resultsmentioning
confidence: 93%
“…DNA repair efficiency as an adaptive trait against solar radiation has been also demonstrated locally at EC I in D. melanogaster (36), and regionally across Israel in wild barley, Hordeum spontaneum (37). The repair efficiency of four thermotolerant and four thermosensitive isofemales lines of D. melanogaster from EC I in Mount Carmel was tested using 2-acetylaminofluorene as the mutagen (36).…”
Section: Resultsmentioning
confidence: 99%